2019
DOI: 10.2147/ijn.s196421
|View full text |Cite
|
Sign up to set email alerts
|

<p>Synthesis, characterization, and mechanistic studies of a gold nanoparticle–amphotericin B covalent conjugate with enhanced antileishmanial efficacy and reduced cytotoxicity</p>

Abstract: BackgroundAmphotericin B (AmB) as a liposomal formulation of AmBisome is the first line of treatment for the disease, visceral leishmaniasis, caused by the parasite Leishmania donovani. However, nephrotoxicity is very common due to poor water solubility and aggregation of AmB. This study aimed to develop a water-soluble covalent conjugate of gold nanoparticle (GNP) with AmB for improved antileishmanial efficacy and reduced cytotoxicity.MethodsCitrate-reduced GNPs (~39 nm) were functionalized with lipoic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 90 publications
(99 reference statements)
5
66
0
Order By: Relevance
“…However, nephrotoxicity is very common due to poor water solubility and aggregation of Amphotericin. So, Kumar et al [60] developed a water-soluble covalent conjugate of gold nanoparticles with a polyene antibiotic Amphotericin B for improved antileishmanial efficacy and reduced cytotoxicity. Macrophages treated with gold nanoparticles with Amphotericin B showed increased immunostimulatory T h 1 (IL-12 and interferon-γ) response compared with standard Amphotericin B.…”
Section: Nanoparticle-based Treatment For Infectious Diseasesmentioning
confidence: 99%
“…However, nephrotoxicity is very common due to poor water solubility and aggregation of Amphotericin. So, Kumar et al [60] developed a water-soluble covalent conjugate of gold nanoparticles with a polyene antibiotic Amphotericin B for improved antileishmanial efficacy and reduced cytotoxicity. Macrophages treated with gold nanoparticles with Amphotericin B showed increased immunostimulatory T h 1 (IL-12 and interferon-γ) response compared with standard Amphotericin B.…”
Section: Nanoparticle-based Treatment For Infectious Diseasesmentioning
confidence: 99%
“…Moreover, these studies showed a size-dependent efficacy of the drug system, with optimal efficacy for 35 nm nanoparticles. Another advantage antibiotic delivery system mediated by AuNPs is the drug-controlled release, where AuNPs loaded with Amphotericin B showed an increase of biocidal efficiency of 78%, with less cytotoxicity and hemolytic toxicity to the host when compared to the antibiotic alone ( Kumar et al, 2019 ).…”
Section: Alternative Antibacterial Therapiesmentioning
confidence: 99%
“…RAW 264.1 cells were maintained in RPMI-1640 medium and infected with promastigotes as described [3]. Parasite-infected macrophages, grown for another 24 h, were treated with varying concentrations of DHF (5-160 μM), DHF-GNP (5-160 μM) and c-GNP (5-80 μM) and chamber slides were washed and supplemented with fresh medium and kept in a CO 2 incubator for another 12 h.…”
Section: Ex Vivo Assay Against Amastigotesmentioning
confidence: 99%
“…Promastigotes (5×10 6 cells/ml) were treated with DHF (120-240 µM), DHF-GNP (40-80 µM) and c-GNP (20 µM) for 12 hours and then harvested. Cells were lysed and the SOD enzyme activity assay was performed as described [3]. AmB (0.…”
Section: Superoxide Dismutase (Sod) Assaymentioning
confidence: 99%